The impact of oil price fluctuations on bank lending power in Iran: An application of GMM approach; El impacto de las fluctuaciones del precio del petróleo en el poder de préstamo bancario en Irán: Una aplicación del enfoque GMM - Mohammad Abdi Seyyedkolaee; Majid Aghaei; Parisa Abbaspoor (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
The abundance of oil resources and the dependence of the state budget on crude oil exports have exposed Iran's single-product economy to oil price fluctuations and its consequences. On the other hand, according to the country's financial system and its being bank-centric, one of the sectors that are constantly affected by oil price fluctuations is the banking system and its performance. To this end, the present study investigated the impact of oil price fluctuations on lending power of specialized banks in Iran using seasonal data from 1999 to 2018 using by Generalized Method of Moments (GMM). The results of this study indicate that during the period under review, oil price fluctuations has been a negative and significant effect (coefficient of -0.01) on the credit growth of specialized banks. In addition, GDP growth and inflation have been, respectively, a positive and negative effect (coefficients of 0.09 and -0.09) on the lending power of specialized banks during the period under review.
Keywords: C23; E44; G21; 330; oil shock; bank lending power; Iranian economy; Generalized Method ofMoments (GMM)